2016
DOI: 10.15585/mmwr.mm6506a5
|View full text |Cite
|
Sign up to set email alerts
|

Notes from the Field: Nosocomial Outbreak of Middle East Respiratory Syndrome in a Large Tertiary Care Hospital — Riyadh, Saudi Arabia, 2015

Abstract: Since the first diagnosis of Middle East respiratory syndrome (MERS) caused by the MERS coronavirus (MERS-CoV) in the Kingdom of Saudi Arabia in 2012, sporadic cases and clusters have occurred throughout the country (1). During June-August, 2015, a large MERS outbreak occurred at King Abulaziz Medical City, a 1,200-bed tertiary-care hospital that includes a 150-bed emergency department that registers 250,000 visits per year.In late June 2015, approximately 3 months after the last previously recognized MERS cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 3 publications
0
64
0
Order By: Relevance
“…Although the most affected countries are rich, such as KSA, Qatar, and UAE, they might look into quicker measures to contain this virus even if those measures are more expensive than vaccines, which take long and laborious efforts. For example, a tertiary hospital in Riyadh, KSA, one of the biggest in the Middle East with 1200 beds and 250,000 visits to the ER per annum, with some VIP royal clinics, was hit by a MERS‐CoV outbreak in August 2015, resulting in 130 cases, with 40% mortality rate . The hospital responded by several actions regardless of the cost, among them closing down the hospital for weeks, building a separate ER for flulike symptoms with several negatively pressurized rooms, and constructing a car drive‐thru screening checkpoint at the entrance of the medical city to direct flulike patients to the new ER without any contact with them.…”
Section: Challenges In Developing Mers‐cov Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the most affected countries are rich, such as KSA, Qatar, and UAE, they might look into quicker measures to contain this virus even if those measures are more expensive than vaccines, which take long and laborious efforts. For example, a tertiary hospital in Riyadh, KSA, one of the biggest in the Middle East with 1200 beds and 250,000 visits to the ER per annum, with some VIP royal clinics, was hit by a MERS‐CoV outbreak in August 2015, resulting in 130 cases, with 40% mortality rate . The hospital responded by several actions regardless of the cost, among them closing down the hospital for weeks, building a separate ER for flulike symptoms with several negatively pressurized rooms, and constructing a car drive‐thru screening checkpoint at the entrance of the medical city to direct flulike patients to the new ER without any contact with them.…”
Section: Challenges In Developing Mers‐cov Vaccinesmentioning
confidence: 99%
“…The hospital was then reopened and had to pay overtime to some staff to catch up with clinic schedules. These responses took only 7 weeks to complete and helped in clearing the MERS‐CoV from this large hospital in an astonishingly short time (personal communication with Dr. Bandar Al Knawy, CEO of King Abulaziz Medical City …”
Section: Challenges In Developing Mers‐cov Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] As of June 26, 2017, there have been 2,029 cases, including a total of 704 deaths, reported to the World Health Organization. [8][9][10][11][12] In addition, hemodialysis units were also highlighted as the focus of multiple documented and undocumented outbreaks in Al-Hasa and Taif, Saudi Arabia (SA). [8][9][10][11][12] In addition, hemodialysis units were also highlighted as the focus of multiple documented and undocumented outbreaks in Al-Hasa and Taif, Saudi Arabia (SA).…”
mentioning
confidence: 99%
“…From the public health perspective, the risk factors for nosocomial outbreaks are overcrowding, lack of proper assessment and triaging of suspected patients, uncontrolled patient movement, absence of patient cohorting and poor compliance with infection control practices by health-care workers (4,9). Evidence has also shown that early recognition of suspected case, appropriate triaging and isolation of suspected patient and rapid implementation of appropriate infection control measures were linked to interruption of transmission in hospitals (10).…”
mentioning
confidence: 99%